Interleukin-17 Genes Polymorphisms are Significantly Associated with Cutaneous T-cell Lymphoma Susceptibility - Karol Kołkowski; Jolanta Gleń; Berenika Olszewska; Monika Zabłotna; Roman J. Nowicki; Małgorzata Sokołowska-Wojdyło (Medical Journals Sweden, 2022)
Tumour microenvironment has an important effect on the progression of cutaneous T-cell lymphomas. Using PCR with sequence-specific primers, this study analysed single-nucleotide polymorphisms in the interleukin-17 genes of 150 patients with cutaneous T-cell lymphoma. GG homozygote rs8193036 A/G of interleukin-17A gene occurred less commonly in the cutaneous T-cell lymphoma group; however, patients with this single-nucleotide polymorphism experience significantly intense pruritus. Conversely, the rs2397084 AG heterozygote of interleukin-17F is more common in the lymphoma population. In addition, there were significant differences in the frequencies of interleukin-17 genotypes when comparing early (Ia to IIa) and advanced stages (IIb, III and IV) of this neoplasms. A similar result has been shown in comparison between Sézary syndrome and mycosis fungoides. The current data may serve as a possible explanation for the increased bacterial infection rates in the course of cutaneous T-cell lymphoma, especially caused by Staphylococcus aureus. In summary, specific single-nucleotide polymorphisms occur with different frequencies between cutaneous T-cell lymphoma and healthy patients. Moreover, genetic predisposition of several interleukin-17 single-nucleotide polymorphisms may be a factor causing impaired immune defence in cutaneous lymphomas.